Control strategies to manage trade-offs during microbial production. (December 2020) - Han, Yichao; Zhang, Fuzhong
Graphical abstract: Highlights: Feedback control can mitigate the impact of the ribosomal cost. Feedback control alleviates metabolic burden caused by engineered metabolic pathways. Metabolic switch resolves conflict between cell growth and engineered pathways. Population quality control can increase the titer and the metabolic stability. Abstract : When engineering microbes to overproduce a target molecule, engineers face multiple layers of trade-offs to allocate limited cellular resources between the target pathway and native cellular systems. These trade-offs arise from limited free ribosomes during translation, competition for metabolic precursors, as well as the negative relationship between production and growth rate. To achieve high production performance, microbes need to spontaneously make decisions in the dynamic and heterogeneous fermentation environment. In this review, we discuss recent advances in microbial control strategies that are used to manage these trade-offs and to improve microbial production. This review focuses on design principles and compares different implementations, with the hope to provide guidelines to future microbial engineering.